Model Pengukuran Kualitas Audit pada Kantor Akuntan Publik di Kota Medan : Pendekatan Partial Least Squares (PLS) - SEM Analisys - Novien Rialdy; M. Firza Alpi; Nadia Ika Purnama; Januri Januri (ITB AAS INDONESIA, 2021)
This study aims to analyze the factors that affect the quality of the audit at the public accounting firm in Medan. This research is a basic research. The research was conducted in several public accounting firms (KAP) in Medan City. The population in this study were all independent auditors who worked at the Public Accounting Firm (KAP) in Medan City, which were registered in the IAI Directory of the Public Accountants Compartment in 2018-2019, totaling 168 auditors. Sampling is done using probability techniques that provide equal opportunities for each member of the population to be elected. Because the number of the study population is small, all populations are sampled (census). The data used in this study are primary and secondary data. Primary data used in this study were obtained by distributing questionnaires to internal auditors who work at the Public Accounting Firm (KAP) in Medan City. The results showed that there was a significant effect of accountability on audit quality. There is a significant effect of competence on audit quality. There is a significant effect of independence on audit quality. There is a significant effect of professional ethics on audit quality. And the professional ethics moderation model is able to strengthen the influence of competence on audit quality.